The last bookshop in London : a novel of World War II - Martin, Madeline (Hanover Square Press, 2021)
"August 1939: London prepares for war as Hitler's forces sweep across Europe. Grace Bennett has always dreamed of moving to the city, but the bunkers and drawn curtains that she finds on her arrival are not what she expected. And she certainly never imagined she'd wind up working at Primrose Hill, a dusty old bookshop nestled in the heart of London. Through blackouts and air raids as the Blitz intensifies, Grace discovers the power of storytelling to unite her community in ways she never dreamed--a force that triumphs over even the darkest nights of the war"--